Determining in vivo Phosphorylation Sites using Mass Spectrometry - Breitkopf, Susanne B. (2012)
Phosphorylation is the most studied protein post-translational modification (PTM) in biological systems since it controls cell growth, proliferation, survival, etc. High resolution/high mass accuracy mass spectrometers are used to identify protein phosphorylation sites due to their speed, sensitivity, selectivity and throughput. The protocol described here focuses on two common strategies: 1) Identifying phosphorylation sites from individual proteins and small protein complexes, and 2) Identifying global phosphorylation sites from whole cell and tissue extracts. For the first, endogenous or epitope tagged proteins are typically immunopurified (IP) from cell lysates, purified via gel electrophoresis or precipitation and enzymatically digested into peptides. Samples can be optionally enriched for phosphopeptides using immobilized metal affinity chromatography (IMAC) or titanium dioxide (TiO2) and then analyzed by microcapillary liquid chromatography/tandem mass spectrometry (LC-MS/MS). Global phosphorylation site analyses that capture pSer/pThr/pTyr sites from biological sources sites are more resource and time-consuming and involve digesting the whole cell lysate, followed by peptide fractionation by strong cation exchange chromatography (SCX), phosphopeptide enrichment by IMAC or TiO2 and LC-MS/MS. Alternatively, one can fractionate the protein lysate by SDS-PAGE, followed by digestion, phosphopeptide enrichment and LC-MS/MS. One can also IP only phospho-tyrosine peptides using a pTyr antibody followed by LC-MS/MS.